Strategic Planning and Environmental Education for Elementary School students, intertwined in the teaching and learning of medical professionals: experience report (Research, Society and Development, 2023)
The knowledge and use of medicinal plants included in Primary Health Care provide countless benefits for individuals, by facilitating access to effective cultural therapy. The curricular content of medical schools presents weaknesses in terms of a holistic view, which determines the training of professionals who are far from regional realities, centered on technicalities and medicalization for all types of illness. This experience promoted Environmental Education in a Municipal Elementary School, located in a community composed of 100% subnormal population, located in the capital of the state of Pará, through the implementation of a garden of medicinal plants called " Living Pharmacy”. It was carried out during the teaching-learning process of Situational Strategic Planning, with the elaboration of an Intervention Project. The operations and programmed actions allowed to initiate discussions on environmental education and the exchange of seedlings between the school community. The verification of the absorption of knowledge was carried out with the application of a test before and after the dialogued exposition, revealing a growth of 28.8% in knowledge about the use of medicinal plants and a growth of 10.6% on the use of medicinal plants by the students' families. The case report produced aims to describe the learning of medical students about planning and executing health promotion actions, analyze the integration of the Federal University of Pará with the Elementary School and with the Community itself and contribute to the production of extensionist actions with Situational Strategic Planning.